Audiologist-Guided Internet-Based Cognitive Behavior Therapy for Adults With Tinnitus in the United Kingdom: A Randomized Controlled Trial. Issue 3 (May 2018) - Beukes, Eldré W.; Baguley, David M.; Allen, Peter M.; Manchaiah, Vinaya; Andersson, Gerhard
Abstract : Objectives: Specialist tinnitus services are in high demand as a result of the negative effect tinnitus may have on quality of life. Additional clinically and cost-effective tinnitus management routes are needed. One potential route is providing Cognitive Behavioural Therapy for tinnitus via the Internet (iCBT). This study aimed to determine the efficacy of guided iCBT, using audiological support, on tinnitus distress and tinnitus-related comorbidities, in the United Kingdom. A further aim was to establish the stability of intervention effects 2-months postintervention. The hypothesis was that iCBT for tinnitus would be more effective at reducing tinnitus distress than weekly monitoring. Design: A randomized, delayed intervention efficacy trial, with a 2-month follow-up was implemented to evaluate the efficacy of iCBT in the United Kingdom. Participants were randomly assigned to the experimental (n = 73) or weekly monitoring control group (n = 73) after being stratified for tinnitus severity and age. After the experimental group completed the 8-week long iCBT intervention, the control group undertook the same intervention. Intervention effects were, therefore, evaluated in two independent groups at two time points. The primary outcome was a change in tinnitus distress between the groups as assessed by the Tinnitus Functional Index. Secondary assessment measures were included for insomnia, anxiety, depression, hearing disability, hyperacusis, cognitive failures, and satisfaction with life. These were completed at baseline, postintervention, and at a 2-month postintervention follow-up. Results: After undertaking the iCBT intervention, the experimental group had a greater reduction in tinnitus distress when compared with the control group. This reduction was statistically significant (Cohen's d = 0.7) and was clinically significant for 51% of the experimental group and 5% of the control group. This reduction was evident 4 weeks after commencing the iCBT intervention. Furthermore, the experimental group had a greater reduction in insomnia, depression, hyperacusis, cognitive failures, and a greater improvement in quality of life, as evidenced by the significant differences in these assessment measures postintervention. Results were maintained 2 months postintervention. Conclusions: Guided (using audiological support) iCBT for tinnitus resulted in statistically significant reductions in tinnitus distress and comorbidities (insomnia, depression, hyperacusis, cognitive failures) and a significant increase in quality of life. These effects remained stable at 2-months postintervention. Further trials to determine the longer term efficacy of iCBT to investigate predictors of outcome and to compare iCBT with standard clinical care in the United Kingdom are required. Registered atclinicaltrials.gov : NCT02370810 on 5/03/2015.